Possibility Degree Method for Ranking Intuitionistic Fuzzy Numbers - Cui-Ping Wei; Xijin Tang (2010 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology, 2010)
In this paper, we study the method of ranking intuitionistic fuzzy numbers. Firstly a possibility degree formula is defined to compare two intuitionistic fuzzy numbers. We prove the ranking order of two intuitionistic fuzzy numbers obtained by the possibility degree formula is the same as the one by using the score function defined by Chen and Tan. Moreover, the possibility degree formula can provide additional information for the comparison of two intuitionistic fuzzy numbers. Based on the possibility degree formula, we give a possibility degree method for ranking n intuitionistic fuzzy numbers and then to rank the alternatives in multi-criteria decision making problems.